SPECTROPHOTOMETRIC STUDY OF COMPLEXES OF SOME INTERCALATORS WITH DOUBLE-STRANDED AND SINGLE-STRANDED NUCLEIC ACIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Interaction of ethidium bromide (EtBr), acridine orange (AO) and non-intercalator methylene blue (MB) with DNA as well as interaction of EtBr and MB with single-stranded synthetic polynucleotides poly(rA) and poly(rU) have been studied. It was revealed that in absorption spectra of EtBr and MB with DNA or single-stranded polynucleotides a real- or pseudo-isosbestic point appears. Particularly, in absorption spectra of the complexes of classical intercalator EtBr with DNA the real isosbestic point is formed, but in the case of non-classical intercalator MB a pseudo-isosbestic point is formed, while in the absorption spectra of their complexes with single-stranded polynucleotides a pseudo-isosbestic point is formed. It was found out that for another classical intercalator AO there is no a real or pseudo-isosbestic point.
Keywords: DNA; synthetic polynucleotides; classical and non-classical intercalators; absorption spectra; binding mode